Classical mesoscopic effect in the resistance of point contacts - Kolesnichenko, Yu. A.; Omelyanchouk, A. N.; Yanson, A. I.; Post, N. van der (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The mesoscopic effect of the dependence of the point-contact conductance on the spatial distribution of the impurities is theoretically studied. It is shown that the resistance dependence on the diameter d is not only determined by the electron mean free path li , but also by the average distance between the impurities. In the case of two types of impurities with different concentrations the mesoscopic effect is predicted for a dirty point contact (d >> li) due to the scattering at specific (e.g., magnetic) impurities with a low concentration. Such contacts were numerically modeled for random distributions of the two types of impurities.